2011
DOI: 10.1002/lary.21921
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial ion transport is suppressed in hypoxic sinonasal epithelium

Abstract: Objectives/Hypothesis Sinonasal respiratory epithelial mucociliary clearance (MCC) is dependent on the transepithelial transport of ions such as Cl−. The objectives of the present study were to investigate the role of oxygen restriction in 1) Cl− transport across primary sinonasal epithelial monolayers, 2) expression of the apical Cl− channels CFTR and TMEM16A, and 3) the pathogenesis of chronic rhinosinusitis (CRS). Study Design In vitro investigation. Methods Murine nasal septal epithelial (MNSE, wild ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 24 publications
3
67
0
Order By: Relevance
“…4145 Inflammation and inspissated secretions congest sinus ostia, consequently leading to hypoxia and mucosal edema, which further impairs MCC. 46 The chronic cycling of inflammation and remodeling promote neutrophil-predominant polyp formation, which only continues to increase with age.…”
Section: Chronic Rhinosinusitis In Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…4145 Inflammation and inspissated secretions congest sinus ostia, consequently leading to hypoxia and mucosal edema, which further impairs MCC. 46 The chronic cycling of inflammation and remodeling promote neutrophil-predominant polyp formation, which only continues to increase with age.…”
Section: Chronic Rhinosinusitis In Cfmentioning
confidence: 99%
“…Importantly, CFTR modulators are also beginning to make their way into clinical studies and represent potential future therapies for mucociliary clearance defects in patients with non-CF CRS. 44,45,106116 …”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
“…In fact, there is evidence that these near-anaerobic conditions may significantly contribute to the pathogenesis of CRS. 30,[32][33][34] Regardless of the mechanism by which mucociliary clearance dysfunction arises, the inability to effectively clear the sinonasal cavity of inhaled pathogens and debris via mucociliary clearance is likely to play a role in the development of this chronic condition. For this reason, therapeutic approaches intended to increase ciliary beating or regulate airway surface liquid secretion remain attractive targets for treatment of CRS.…”
Section: Mucociliary Clearance: Mopping Away Bugs and Debrismentioning
confidence: 99%
“…A previous study showed that cellular activities such as DNA replication may depend on oxygen concentration, so hypoxia might result in a decrease in the rate of cell proliferation [20]. In other studies, it was found that mucus hypersecretion can lead directly to the obstruction of the airways, resulting in poor mucociliary clearance and poor tissue oxygenation [21, 22]. These findings have lent support to the fact that high concentrations of CP may considerably impair the airway epithelial function by forming a thickened gel on the epithelial surface.…”
Section: Discussionmentioning
confidence: 99%